Revision of Indian Cyphochilus Waterhouse, 1867 (Coleoptera: Scarabaeidae: Melolonthinae) with description of two new species - Sreedevi, Kolla; Sahoo, Kishore Chandra; Ajaykumara, Kattigehalli Math; Boopathi, Thangavel; Sushil, Satya Nand; Sabatinelli, Guido (Zootaxa, 2025)
The genus Cyphochilus Waterhouse, 1867 (Coleoptera: Scarabaeidae: Melolonthinae) comprises 62 species worldwide. A comprehensive examination of 260 specimens from India—including type material and additional specimens from institutional and private collections—confirms the presence of eight species in the country. This includes two new species, Cyphochilus kukriana Sreedevi, Sahoo & Sabatinelli, sp. nov. and C. pentaphysia Sreedevi, Sahoo & Sabatinelli, sp. nov., and the first Indian record of C. tenzingyatsoi Sabatinelli, 2020. The following synonymy is proposed: Cyphochilus niveosquamosus (Blanchard, 1851) = C. oberthueri Brenske, 1903. Based on the original descriptions and type localities, C. manipurensis Nonfried, 1893 and C. waterhousei Brenske, 1903 are also considered potentially referable to C. niveosquamosus. A systematic account, including detailed illustrations of the habitus and aedeagus for all species, along with an updated checklist of Indian Cyphochilus, is provided.